2007
DOI: 10.1101/gad.1575307
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal signaling modulates protein homeostasis in Caenorhabditis elegans post-synaptic muscle cells

Abstract: Protein homeostasis maintains proper intracellular balance by promoting protein folding and clearance mechanisms while minimizing the stress caused by the accumulation of misfolded and damaged proteins. Chronic expression of aggregation-prone proteins is deleterious to the cell and has been linked to a wide range of conformational disorders. The molecular response to misfolded proteins is highly conserved and generally studied as a cell-autonomous process. Here, we provide evidence that neuronal signaling is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
133
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(140 citation statements)
references
References 51 publications
7
133
0
Order By: Relevance
“…Significantly, we observed a nonautonomous influence of ddlc1 on autophagy in muscle, and this was associated with decreased neuromuscular junction synapse numbers. These data are consistent with the nonautonomous influence of neuronal function on muscle physiology in a Caenorhabditis elegans model of polyglutamine disease (43). In addition, these data are in accordance with the recent demonstration that autophagy in motor neurons regulates synapse development via clearance of Highwire in flies (44).…”
Section: Resultssupporting
confidence: 81%
“…Significantly, we observed a nonautonomous influence of ddlc1 on autophagy in muscle, and this was associated with decreased neuromuscular junction synapse numbers. These data are consistent with the nonautonomous influence of neuronal function on muscle physiology in a Caenorhabditis elegans model of polyglutamine disease (43). In addition, these data are in accordance with the recent demonstration that autophagy in motor neurons regulates synapse development via clearance of Highwire in flies (44).…”
Section: Resultssupporting
confidence: 81%
“…In particular, picrotoxin could cause an imbalance in protein homeostasis in postsynaptic muscle cells through its effect as a GABA A R blocker, consistent with a study by Garcia et al (2007) which stated that modifications that alter the balance of ACh and GABA at the neuromuscular junction (NMJ) cause an increase in polyQ aggregation on C. elegans strains expressing chimeric polyQ fusion proteins to yellow fluorescent protein (YFP).…”
Section: Discussionsupporting
confidence: 55%
“…Additionally, several reports have shown that UNC-49 inactivation provokes an imbalance between ACh and GABA in favor of ACh, causing a defective protein folding and aggregation and therefore inducing a protein homeostasis breakdown in postsynaptic muscle cells (Garcia et al 2007;Gidalevitz et al 2011;Prahlad and Morimoto 2009), which triggers a heat shock response, including a transcription rapid of hsp genes dependent on HSF-1. For this to happen, the misfolding protein accumulation could interact with a complex of monomeric HSF-1 and HSPs to induce its cleavage.…”
Section: Discussionmentioning
confidence: 99%
“…These findings therefore indicate that traditional neurotransmitters such as ACh, GABA, or neuropeptides are also not involved in the UNC-18 function. The normal VenusTUNC-6 localization observed in the unc-25 mutant indicated that the muscle homeostasis regulated by GABA (Garcia et al 2007) is not involved in the UNC-18 function. It is also unlikely that the abnormal VenusTUNC-6 localization in unc-18 resulted from the severe defect in muscle contraction observed in this mutant, since the unc-13 mutant, which also displayed a paralyzed phenotype, showed normal localization of VenusTUNC-6.…”
Section: Discussionmentioning
confidence: 94%